Baby bear : finger puppet book - Huang, Yu-Hsuan. (California : Chronicle Books, 2016)
What does Baby Bear eat when he's hungry? Follow along with this cute baby animal as it experiences its world, from playtime to bedtime. This simple, comforting story features a permanently attached plush finger puppet and peek-a-boo holes in every page, giving parents and children a fun, interactive way to play and read together.